Exchange Rate, Tax Minimization, Debt Covenant on Transfer Pricing in Corporate Governance Moderation (in Manufacturing Companies Listed on the Indonesia Stock Exchange in the 2020-2023 Period) - Dinar Karmila; Imas Kismanah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine the effect of Exchange Rate, Tax Minimization, Debt Covenant on Transfer Pricing in Corporate Governance Moderation (In Manufacturing Companies Listed on the IDX for the 2020-2023 Period). This study uses a quantitative approach. The population in this study includes manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. The sampling technique used is Purposive Sampling. Based on the established criteria, 26 company samples were obtained. The type of data used is secondary data obtained from the official website of the Indonesia Stock Exchange. The method used in this study is panel data regression analysis. The results of this study indicate that simultaneously Exchange Rate, Tax Minimization, Debt Covenant together have an effect on Transfer Pricing and Corporate Governance can moderate this effect. while partially Exchange Rate does not have a significant effect on Transfer Pricing while Tax Minimization and Debt Covenant have a significant effect. Corporate Governance is proven to moderate the influence of Tax Minimization and Debt Covenant but does not moderate the influence of Exchange Rate.